Development of the 500 kW and 1 MW ORC turbine flow parts - Rusanov, R.; Szymaniak, M.; Rusanov, A.; Lampart, P. (Проблемы машиностроения, 2017)
There paper presents two types of developed ORC turbines. The silica oil (MDM) is used as the working media. Proposed turbines are developed for electric power in 500 kW and 1 MW. For the designing of that turbines there were only one geometric constraint: the minimum height of the blade – 20 mm. The final 3D calculations of all turbine stages are provided with accounting the real properties of working media. Gasdynamic efficiency of the developed turbine flow parts is adequate for the such type of power machines.